2017
DOI: 10.3390/molecules22050775
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Nanotubular TiO2 Photoanodes Grown Directly on FTO Substrates

Abstract: This work describes the preparation of transparent TiO2 nanotube (TNT) arrays on fluorine-doped tin oxide (FTO) substrates. An optimized electrolyte composition (0.2 mol dm−3 NH4F and 4 mol dm−3 H2O in ethylene glycol) was used for the anodization of Ti films with different thicknesses (from 100 to 1300 nm) sputtered on the FTO glass substrates. For Ti thicknesses 600 nm and higher, anodization resulted in the formation of TNT arrays with an outer nanotube diameter around 180 nm and a wall thickness around 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Recently, the anodization of titanium thin films deposited on glass substrates via different Physical Vapor Deposition methods [18,25], especially magnetron sputtering, have proven to be a promising route to achieve devices with high stability and performance [16,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the anodization of titanium thin films deposited on glass substrates via different Physical Vapor Deposition methods [18,25], especially magnetron sputtering, have proven to be a promising route to achieve devices with high stability and performance [16,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, highly ordered TiO 2 nanotube arrays are typically grown by electrochemical anodization of titanium foils [23]. However, fully transparent photoelectrodes or photonic devices are highly desirable in many applications including photovoltaics and PEC cells [18,24]. For instance, TNT reaching transparency higher than 65% and producing stable photocurrent can be employed in PEC tandem cells, in which the illumination from the support-semiconductor interface is a required condition, enabling the efficient excitation of both photoanode and photocathode materials [24].…”
Section: Introductionmentioning
confidence: 99%
“…As already discussed above the substrate temperature during the deposition is considered as one of the most important parameter that should be adjusted to achieve a good adhesion of Ti films to the substrate. However, the works done by Buettner et al [ 16 ], Pausova et al [ 1 ] and Krysa et al [ 33 ] have shown that not only the substrate temperature, but also the morphology of the deposited Ti films play a major role in good adhesion of TNTs layer. This section discusses the impact of the deposited Ti thickness on the geometrical features of anodic semitransparent TNTs.…”
Section: Effect Of the Deposited Ti Thickness On Tnts Adhesion And Ge...mentioning
confidence: 99%
“…This indicates a significant improvement in the absorption capacity towards the visible range of the semitransparent material after CdS quantum dots decoration. Moreover, a good transmittance, about 90%, in the visible range was achieved by Paušová et al [ 1 ] after the annealing of TNTs grown on FTO at 500 °C.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation